Changes in Periodontal Blood Supply in Patients with Maxillomandibular Anomalies and Vestibular Architectonic Disorders during Complex Treatment - Derkach Лілія; Makhlynets Наталія; Kohut Володимир (Actual Dentistry, 2026)
The aim of the study was to evaluate the features of local blood circulation in the tissues of the oral vestibule in patients with dentofacial anomalies associated with architectonic defects. Research methods: a comprehensive examination and treatment of 60 adolescents (age category 15–17 years) with diagnosed acquired anomalies and deformations of the dentofacial system was carried out. All study participants were divided into two main groups: The first group (n = 30): surgical intervention (connective tissue cord plastic) was performed according to the classical method, which involved healing of the surgical wound by secondary tension. Subgroup 1A (n = 15): in the postoperative period, only chlorhexidine-denta was used. Subgroup 1B (n = 15): pharmacological support included a combination of Chlorhexidine-Denta with Gengigel. The second group (n = 30): correction was performed according to the author’s developed method aimed at wound healing by primary tension. Subgroup 2A (n = 15): Chlorhexidine-Denta was prescribed. Subgroup 2B (n = 15): a combined regimen was used—Chlorhexidine-Denta and Gengigel. To compare the results, a control group (n = 15) was formed, which included individuals without dentofacial anomalies, bad habits and signs of periodontal diseases. Objective assessment of the hemodynamic state was performed by rheography using the software and hardware complex Rheograph DX and DX-Complex Regina 2002. Registration of indicators was carried out using specialized dental electrodes created in cooperation with the enterprise DX-Complex (Kharkiv, Ukraine). Monitoring of rheographic parameters was performed in stages: before the start of therapy and at 1, 6, and 12 months after surgery. Scientific novelty: It has been established that patients with dentofacial anomalies and concurrent architectonic defects of the oral vestibule exhibit a distinct deficiency in regional blood supply and deterioration of tissue trophism. This is evidenced by pathological changes in hemodynamic parameters: an increase in peripheral vascular resistance (PVR), venous vascular tone (VVT), and venous outflow (VO), with a simultaneous decrease in the rheographic index (RI) and volumetric blood flow (VBF) (p < 0.05). A direct correlation between the qualitative characteristics of rheograms and their quantitative values was revealed. It was noted that despite the general positive dynamics in all study groups after treatment, the most statistically significant approximation of indicators to the physiological norm (comparison group) was observed in Subgroup 2B (p < 0.05), where the author’s surgical correction method was applied. Conclusions. A comprehensive analysis of qualitative and quantitative rheography parameters confirmed that patients aged 15–17 years with combined pathology (dental anomalies and violations of the architectonics of the vestibule of the mouth) are characterized by pronounced insufficiency of regional blood circulation, stagnation in periodontal tissues and difficulty in venous outflow. The use of the developed method of surgical intervention using palatal mucosal grafts in combination with adjuvant therapy with Gengigel provides effective normalization and stable restoration of the functional state of the vascular bed both in the near and long-term observation periods.